Interpersonal Communication Patterns Of Street Children With Peers (Ethnographic Study of Street Children in the Ramayana Area of Kupang) - Aditya Rahisa Mutia; Petrus Ana Andung; Felicianus Efrem Jelahut (Jurnal Komunikasi, 2025)
This research aims to understand the interpersonal communication patterns that occur between street children and their peers in Kupang City, as well as to identify the forms of communication that exist between street children and their peers. The research methodology used in this study is qualitative research with the ethnographic study method and the application of the FIRO-B (Fundamental Interpersonal Relation Orientation-Behavior) theory. The data collection techniques employed in this research include observation, interviews with 5 informants, and documentation. The research results indicate that the interpersonal communication pattern between street children and their peers uses Circular Communication pattern in communicating with fellow street children within the group, and also a two-way Linear Communication pattern when communicating with other street children. However, in communicating with non-street children peers, the communication pattern established tends to fail due to the gap between street children and non-street children peers. The forms of communication that occur between street children and their peers are Verbal Communication and Nonverbal Communication among fellow street children. Meanwhile, the forms of communication between street children and non-street children peers are Verbal Communication, Nonverbal Communication, and Digital Communication.